Crack propagation trajectory for kenaf fibre composite under quasi static loading - Nurul Alya Zahari, Nurul Alya Zahari; Zaleha Mohamad, Zaleha Mohamad (2020)
The cracking of the composites are worthy the attention in order to expect in which manner of failure might occur. This matter should be not underestimated because of a safe structure may fail with even microscopic flaws. The crack propagation trajectory and effects of the hole in woven and non-woven fibre orientations for epoxy based kenaf composites under quasi static loading are investigated. The shape of the work specimens is square thin plate with thickness of 3 mm. There are two types of orientations of work specimen used which are the non-woven random and plain woven with 0° and 90° fibre orientation. These work specimens made by hand lay-up method. There are three setting conditions of the work specimen used in this research such as single edge crack, single edge crack with hole, and double edge crack with two holes. The experiments of tensile tests were carried out to determine the strength of the epoxy based kenaf composites. The specimens were subjected to a concentrated load at the upper edge and fixed at the lower edge. From the data attained, indicated that fibre orientation has a significant role in defining the ultimate tensile strength. The main objective of this research is to investigate the crack propagation trajectory for epoxy based kenaf composites under quasi static loading. It shows that from the results obtained, the crack trajectories for single edge crack is a straight line. However, the existence of the hole rearrange the stress or strain field. The crack will curved towards the hole. Meanwhile, for double edge cracks with two holes, the cracks move to the near hole. The cracks then reoriented horizontally as the cracks have reformed the stress distribution at each other’s tip. After that, the cracks then captivated again by the opposite holes and curved towards the holes. It was found that there is no significant difference between the crack propagation for non-woven and woven fibre orientation samples.